An Analysis Of Learning Method In Implementasi Kurikulum Merdeka By Mandiri Belajar At Eleventh Grade Of SMK Swasta Prama Artha - Semaria Eva Elita Girsang; Bismar Sibuaea; Indah Suruani (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
This research is to describe the learning method used by teacher in Implementasi Kurikulum Merdeka by Mandiri Belajar. This type of research is descriptive qualitative with the research location at SMK Swasta Prama Artha. The data collection methods used are observation, interviews, and documentation. The data analysis technique is descriptive qualitative analysis, namely data reduction, presentation, and drawing conclusion. The results of the research found that the learning methods used by teachers are integrative learning method with using the four phases: (1) Phase 1: describing, comparing, and investigating patterns (2) Phase 2: Explaining similarities and differences (3) Phase 3: marking an additional step in developing students' ability to process information (4) Phase 4: generalization to form broad relationships. The researcher suggests that teachers apply this learning method in the learning process